HUBUNGAN STRES KERJA DENGAN KEJADIAN BURNOUT PADA PERAWAT DI INSTALASI RAWAT INAP RSUD CILEUNGSI KABUPATEN BOGOR - Sherly Agatha, (2022)
Burnout is a form of individual response to stress-causing factors that occur in the workplace. During the process of providing health care, nurses are faced with complex situations. Stressors that occur continuously can result in physical, mental, and emotional fatigue which can lead to burnout. This study aims to determine the relationship between work stress and the incidence of burnout in nurses at Cileungsi Hospital. The research design is quantitative with a cross sectional approach. The sampling technique used in this research is total sampling with 70 respondents. The data analysis applied was the Chi-Square test at 95% CI. The results of statistical tests showed that there was no significant relationship between age (p-value = 0.698), gender (p-value = 1,000), education level (p-value = 0.105), years of service (p-value = 0.461), and marital status (p-value = 0.587) with the incidence of burnout in nurses at the Inpatient Installation of Cileungsi Hospital. In addition, it was also found that there was a significant relationship between work stress and burnout in nurses at the Inpatient Installation of Cileungsi Hospital (p-value = 0.000). Burnout in nurses can be prevented by improving the work system or by providing an appropriate division of tasks. Keywords : Work Stress, Nurses, Burnout